Innovation in learning anesthesia nursing care based on the android application “SIASENA” - Annisa, Rully; Ching Cing, Marta Tania Gabriel; Purwanto, Lahan Adi (Riset Informasi Kesehatan, 2025)
Background: Anesthesiology Nursing Care Services (ASKAN) are used to refer to a series of comprehensive care activities for patients who cannot help themselves due to impaired body function, especially during the anesthesia service process before, during, and after the procedure, or in other situations. The provision of care is carried out through an anesthesia management method approach, which includes the stages of assessment, analysis, problem determination, action/intervention planning, implementation, and evaluation. The implementation of anesthesiology nursing care services (ASKAN) is carried out independently and involves collaboration with anesthesiology specialists, surgeons, and other professional health workers to provide services to patients. The implementation of ASKAN requires anesthesia nurses as one of the health workers involved in providing health services to continue to improve their knowledge and skills. With mobile learning, students have access to learning materials and information from various places and at any time. They are not limited to a certain time or location to learn. The purpose of this study was to produce a prototype and learning model for mobile learning, namely the "SIASENA" application. Method: This study uses the research and development (R&D) method, which is a research approach intended to create a particular product and test the effectiveness of the product. Results: The process of creating the SIASENA application in the form of a complete application. Includes the development of program code which is carried out by writing the SIASENA application source code according to the specifications and designs that have been made. This activity includes the development of user interfaces, application logic, and integration with databases. The integrated development environment (IDE) used is android studio. The database management system (DbMS) used in building the database is MySQL. To integrate the android-based SIASENA application with the MySQL database using web service technology written in the PHP programming language using the visual studio code editor. In this activity, all application modules and components are combined into one complete system unit. After that, validation was carried out by media experts and material experts, followed by a trial on respondent partners, namely anesthesia nursing students. Conclusion: The creation of an android-based learning application "SIASENA" as an innovation in learning anesthesia nursing care, especially documentation, has been successful. With this application, it is hoped that it can support learning anesthesia nursing care in anesthesia nursing educational institutions.